The importance of ions in low pressure PECVD plasmas - Michelmore, Andrew; Whittle, Jason D.; Short, Robert D. (Frontiers in Physics, 2015)
Plasma enhanced chemical vapour deposition (PECVD) can be used to fabricate surfaces with a wide range of physical and chemical properties and are used in a variety of applications. Despite this, the mechanisms by which PECVD films grow are not well understood. Moreover, the species which contribute to film growth can be considered quite differently depending on the process. Particularly for functionalized plasma polymer films, the growth mechanisms are considered with respect to the chemistry of the depositing species, ignoring the physics of plasmas. Here we analyse the role ions play in the deposition of three common classes of depositing plasmas, and how these closely related fields treat ions very differently.